2019
DOI: 10.1155/2019/8637970
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Oxidative Stress as a Link between Diabetes Mellitus and Major Depressive Disorder

Abstract: Both conditions, major depressive disorder (MDD) and diabetes mellitus (DM) are chronic and disabling diseases that affect a very significant percentage of the world’s population. Studies have been shown that patients with DM are more susceptible to develop depression, when compared to the general population. The opposite also happens; MDD could be a risk factor for DM development. Some mechanisms have been proposed to explain the pathophysiological mechanisms involved with these conditions, such as excess of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 60 publications
1
37
0
2
Order By: Relevance
“…The mitochondrion is an organelle that supplies a large amount of energy using an electron transport chain and oxidative phosphorylation and contributes to cellular activities. However, this process also generates reactive oxygen species (ROS) which causes oxidative damage to mitochondrial lipids, DNA, and proteins [5, 6]. Oxidative stress is considered as a major environmental factor in aging [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrion is an organelle that supplies a large amount of energy using an electron transport chain and oxidative phosphorylation and contributes to cellular activities. However, this process also generates reactive oxygen species (ROS) which causes oxidative damage to mitochondrial lipids, DNA, and proteins [5, 6]. Oxidative stress is considered as a major environmental factor in aging [29].…”
Section: Discussionmentioning
confidence: 99%
“…Excess ROS can be utilized by endogenous antioxidant such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and other enzymes. The overproduction of ROS is related to oxidative stress and can cause damage to biological molecules [5, 6]. Various literatures reported that natural or synthetic antioxidants can be used to counter harmful effects of oxidative stress [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for depression include adverse life events, external environmental stress, cognitive impairment, depressed parents, social dysfunction, and being female (Hammen, 2018). Patients with malignant tumors, diabetes, chronic physical pain, or cardiovascular and cerebrovascular diseases also had higher rates of depression than healthy controls (Bortolato et al, 2017; Hare et al, 2014; Kales, Maixner & Mellow, 2005; Réus et al, 2019; Sheng et al, 2017). Thus, both structural and functional disorders, especially in the brain, may contribute to depression.…”
Section: Introductionmentioning
confidence: 96%
“…Oxidative stress is defined as an imbalance between oxidation and anti-oxidation in the body where the endogenous antioxidants are not able to counteract the oxidative dysregulation of lipids, protein, DNA and cellular structures [7]. Oxidative stress has been found to be closely related to metabolism in recent years [8,9].…”
mentioning
confidence: 99%